Development and implementation of a nursing students’ simulation program for the initial assessment of trauma patients - Kim, Min Su; Chu, Min Sun (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to develop and implement a simulation-based training program designed to enhance nursing students’ competency in the initial assessment of trauma patients while providing a controlled and safe learning environment. The simulation program was structured based on the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, incorporating multiple levels of fidelity into the simulation design. A traffic accident scenario was selected to simulate realistic trauma patient assessments. The program was developed between October 2022 and February 2023 and was subsequently implemented on June 23–24, 2023, with 21 nursing students from a university in Seoul. The program’s effectiveness was assessed through the evaluation of changes in confidence levels, engagement in practice, and participation experiences. Statistical analyses were conducted using SPSS 24.0. Confidence levels before and after the program were compared using the Wilcoxon signed-rank test, and engagement in practice was analyzed using descriptive statistics, including means and standard deviations. Qualitative content analysis was employed to examine participation experiences. The results demonstrated a significant improvement in confidence levels following program completion (Z = –3.92, p < .05). The highest engagement in simulation practice was reported in autotelic experiences. The qualitative analysis identified key themes, including "disorientation in trauma patient situations," "approaching collaborative nursing," and "enhanced motivation for learning." Scenario-based education incorporating varying levels of fidelity was found to be an effective pedagogical approach for improving nursing students’ competencies in trauma patient assessment and facilitating rapid clinical decision-making in high-pressure environments. These findings underscore the value of integrating simulation-based education into nursing curricula to enhance students’ clinical preparedness and confidence in managing trauma cases. Future research should explore the integration of real-world clinical experiences with simulation-based training to further optimize educational outcomes and bridge the gap between theoretical knowledge and practical application.